Developing the Writing Skills in English Language: The Growing Importance of English Language Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
India is emerging as a worldwide leading player in science, technology, space, business, and company sectors furthermore as in education. Critics have started seeing India as superpower or the following dominating country after the US of America. It’s reported its presence all told type worldly communication. During this changing periphery, the knowledge of West Germanic is crucial, as we've to speak in English with the remainder of the globe. English has been chosen as a medium of conversation among the fast growing countries. As per the opinion of the primary Prime Minister of India, Pandit Nehru that English could be a mirror or a window to peep in to the affairs of world. Education may be a process of enlightment and empowerment by which the individuals are able to secure better quality life. Today, education is global and a multiple social services, which must rewarded human resources fullness, commitment and freedom. The current day education is geared toward the expansion of body, mind, intellectuality, and soul. Children are humanity’s greatest wealth. Many students venture out of our country in pursuing of upper education. Hence we must always welcome modern knowledge system supported old culture. It’s widely accepted incontrovertible fact that knowledge must be acquired and supplemented by a lifelong learning and retaining system. The people everywhere the globe have come to depend upon English for his or her economic and social well-being. Accordingly, English language Teaching and Learning has more attention 6 than the other learning. During this regard, Kachru mentions Just some centuries ago, English was spoken by just five to seven million people on one, relatively small island, and therefore the language consisted of dialects spoken by monolinguals. Today there are more non-native users of English, and English has become the linguistic key used for opening borders it's a worldwide medium with local identities and messages.